Structure of the training program during the COVID-19 confinement in Spanish professional football, a coach survey - Asín-Izquierdo, I.; Gutiérrez-García, L.; Zapardiel, J. C.; Chena, M. (The Physician and Sportsmedicine, 2021)
COVID-19 has produced an exceptional situation for sport due to confinement and restrictions. The usual training programs and competition have been interrupted in world football, requiring an adaptation of training to the new situation. Objectives: To describe and analyze the training programs carried out during the COVID-19 forced confinement in men´s professional football in Spain. Methods: Observational Study based on a telematic ad-hoc questionnaire developed to meet the objective of the study. The sample consisted of thirty-six coaches representing thirty-six professional men`s soccer teams in the Spanish first and second division. Results: Training programs developed during confinement prioritized conditioning and functional emphasis, in addition to general and non-specific resistance training, due to contextual limitations. Conclusion: The structure of training during the COVID-19 confinement was limited by contextual circumstances. This study has made possible to record the training and strategies used in professional football during a confinement due to a worldwide state of alarm, with the aim of resuming competitive activity in the best possible conditions.